Adjustment processes and fit perceptions as predictors of organizational commitment and occupational commitment of young workers - Nägele, Christof [Verfasser]; Neuenschwander, Markus P. [Verfasser] (My University, 2014)
"Task mastery and social integration have been shown to be key elements in the adjustment process of young workers during the entry phase in a new organization. We analyzed the effect of task mastery and social integration on organizational commitment and occupational commitment of young workers in a longitudinal study. Fit perceptions before organizational entry were included as predictors of the adjustment process and commitment. Data were drawn from a sample of 550 young workers in the transition from school to work before and in the first six months after organizational entry. Results show the importance of the positive change of social integration as predictor of organizational commitment and occupational commitment and additionally the importance of the pre-entry occupation-person fit on occupational commitment. The results have implications for the understanding of the organizational entry process of young workers and its dependency on the adjustment process and pre-entry fit perception." (Authors' abstract, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; P 2.3 Auszubildende; T 3.4 Befragung; I 2.2.1 Westeuropa; Betriebliche Berufsausbildung; Auszubildender; Ausbildungszufriedenheit; Soziale Anpassung; Soziale Integration; Berufliche Sozialisation; Empirische Untersuchung; Befragung; Schweiz